The outpatient situation in the Cape Peninsula - Taylor, Stephen Paul (Department of Medicine, 2025)
This dissertation is based on a study commissioned by the Cape Provincial Administration's hospital department into ambulatory care in the Cape Peninsula. The aim of the study was to investigate the whole picture of the provision of outpatient services by that hospital department in the Cape Peninsula. The investigation was to specifically isolate and assign problem areas and propose realistic solutions in order to overcome the "implementation gap" between research and policy implementation. The focus of the investigation was to be the Day Hospital Organisation and Paediatric Care. This very broad aim was to be met by five specific objectives which were (i) to determine the demographic characteristics of the population of the Cape Peninsula, (ii) to determine utilisation of ambulatory services; (iii) to quantitate problems, determine resources used, and (iv) determine attitudes to the service as perceived by medical staff. The study consisted of over 20 individual epidemiological investigations. These investigations varied in methods from cross-sectional analyses to simple descriptive epidemiology. Two substantial descriptive studies were performed. The· first was a crosssectional study of doctors' attitudes and practices in all hospital / day hospital ambulatory settings in the Cape Peninsula. The second was a descriptive study of all patients who attended the Day Hospital Organisation in 1987. An overall picture was obtained as to utilisation rates, demography, resources deployed and attitudes of staff. A comprehensive literature review revealed a relative dearth of information concerning the subject in South Africa. Where information was available, it was piecemeal and often operationally directed. A review of organisational and other factors impacting on ambulatory services revealed that although past commissions and National Plans have had noble objectives, those objectives were never attained. Major findings of the study were that although overall attendances to the service had increased by 10 % between 1980 and 1987, the attendance number by whites had decreased by 16 % while that of blacks had increased by 62 %. The Day Hospital Organisation had had a static workload which had only increased with the addition of new clinics in the latter years. The rapid rate of increased attendances placed a burden on many hospitals. Four organisations were rated to have a crisis which in order of severity were: Red Cross Hospital, Conradie Hospital, Day Hospital and Groote Schuur Hospital.